Classi dirigenti nell'Italia unita: tra gruppi e territori - De Prospo, Mario (Clio. Saggi di scienze storiche, archeologiche e storico-artistiche, 2022)
This work arises from the presentations held during the research seminar of the Italian Society for the Study of Contemporary History (SISSCO) titled Ruling classes and spaces in the contemporary period. Asymmetries between centres and peripheries, continuities and discontinuities. The Italian case (1861-2015), organized between the end of 2016 and the beginning of 2017 and coordinated by the Centro di ricerca "Guido Dorso" per lo studio del pensiero meridionalistico. The volume is conceived as a test for the vitality of a field of study of historiography on contemporary Italy: that on the various sectors of the country's elite from Risorgimento to present days. This effort has been made through direct discussion between scholars, paying particular attention to the territorial diversities and the political and institutional changes. The work offers a rich and multifaceted collection of essays, focusing on different geographical areas and segments of the Italian ruling classes, based on different methodological approaches and various sources.